Pengaruh Status Sosial Ekonomi Keluarga Terhadap Minat Siswa Melanjutkan Studi Ke Perguruan Tinggi (Studi Siswa Kelas XII IPS SMAN 4 Gorontalo) - Nur Afni Laparako; Sudirman; Frahma Bumulo; Abdulrahim Maruwae (Yayasan Pendidikan Sudirman Mandiri, 2025)
This Study aims to determine whether family socioeconomic status influences students’ interest in pursuing higher education, focusing on 12th-grade Social Science students at SMAN 4 Gorontalo. The research employed a desctiptive quantitative approach with a sample size of 38 students. The data collection instrument used was a questionnaire, and the data were analyzed using simple linear regression analysis. The result of the data analysis indicate a significant influence of family socioeconomic status on students’ interest in pursuing to higher education. The study found that 13.7% of students’ interest in pursuing highter education in influenced by their family’s socioeconomic status while the remaining 86.7% is influenced by other variables not examined in this study.